Euphemisms, proverbs, allusions, and cognition: A study of two poems by Antonio Machado - Chamizo-Domínguez, Pedro J.; Bretones Callejas, Carmen M. (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Among the various devices that conform a given writer’s style (i.e. syntactic, semantic, and so on), we will ll analyse in this paper two of them, allusion and euphemism. And so, in order to illustrate how, by means of these stylistic devices, A. Machado gets cognitive effects and criticizes two given philosophical systems in two extremely short poems. Euphemisms and allusions do perform meanings in cognitive domains not merely aesthetic or rhetorical ones. And this function is related to previous knowledge and presuppositions of the speakers. For that reason several levels of readings are possible according to the different levels of presuppositions made by speakers.